Deep learning in Cancer Diagnostics: a feature-based transfer learning evaluation - Arzmi, Mohd Hafiz; Abdul Majeed, Anwar P.P.; Musa, Rabiu Muazu; Mohd Razman, Mohd Azraai; Gan, Hong-Seng; Mohd Khairuddin, Ismail; Ab. Nasir, Ahmad Fakhri (Springer, 2023)
This book highlights the use of state-of-the-art Deep learning (DL) techniques in cancer diagnosis. It includes the diagnosis of four types of common cancers, i.e., breast, lung, oral and skin. This book also discusses the use of DL methods in combination with imaging techniques to identify cancer correctly.